Risk factors for lymph node metastases of facial cutaneous squamous cell carcinoma. Issue 8 (August 2017) - Obermeier, Katharina; Tröltzsch, Matthias; Ehrenfeld, Michael; Smolka, Wenko
Abstract: Purpose: Determining the risk factors for lymph node metastases of facial cutaneous squamous cell carcinoma and identifying their value for predicting nodal spread. Material and methods: Data on 99 patients were examined retrospectively. Conditions such as tumor staging, tumor thickness, location, histological grading, R1-resection, local recurrence, lymph node metastases, and neurovascular and lymphovascular invasion were evaluated. Statistical analysis was performed using a logistic regression analysis and Fisher's test. Results: Logistic regression analysis indicates that poor differentiation, R1-resection, and periorbital location are high risk factors for nodal spread in facial cutaneous squamous cell carcinoma. Conclusion: Patients who show poorly differentiated facial cutaneous squamous cell carcinoma and/or have had previous R1-resection might benefit from treatment of regional lymph nodes.